The Home Use of Probiotics and Paraprobiotics for the Maintenance of Tongue Eubiosis: A Case Report - Salvatore Cannizzaro; Carolina Maiorani; Andrea Scribante; Andrea Butera (Case Reports in Dentistry)
Conclusion: Systematic removal of bacterial biofilm and the use of probiotics and paraprobiotics can be useful in the prevention and treatment of halitosis.